2003
DOI: 10.1046/j.1365-313x.2003.01819.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a stress‐inducible aldehyde dehydrogenase gene from Arabidopsis thaliana in transgenic plants improves stress tolerance

Abstract: SummaryIn plants, oxidative stress is one of the major causes of damage as a result of various environmental stresses. Oxidative stress is primarily because of the excessive accumulation of reactive oxygen species (ROS). The ampli®cation of ROS damage is further stimulated by the accumulation of toxic degradation products, i.e. aldehydes, arising from reactions of ROS with lipids and proteins. Previously, the isolation of dehydration-inducible genes encoding aldehyde dehydrogenases (ALDHs) was reported from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
265
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 392 publications
(277 citation statements)
references
References 56 publications
10
265
0
2
Order By: Relevance
“…MDA is an end product of polyunsaturated fatty acid oxygenation and is a commonly used biomarker for assessing lipid peroxidation (Janero 1990;Moore and Roberts 1998). In plant cells, environmental stressors, such as drought, salinity, extreme temperatures and heavy metals, cause a rapid and excessive accumulation of reactive oxygen species that further cause lipid peroxidation (Sunkar et al 2003). The levels of lipid peroxidation in plant cells were assayed with the thiobarbituric acid test, which determines the amounts of MDA as end product of lipid peroxidation (Heath and Packer 1968;Loreto and Velikova 2001;Sunkar et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…MDA is an end product of polyunsaturated fatty acid oxygenation and is a commonly used biomarker for assessing lipid peroxidation (Janero 1990;Moore and Roberts 1998). In plant cells, environmental stressors, such as drought, salinity, extreme temperatures and heavy metals, cause a rapid and excessive accumulation of reactive oxygen species that further cause lipid peroxidation (Sunkar et al 2003). The levels of lipid peroxidation in plant cells were assayed with the thiobarbituric acid test, which determines the amounts of MDA as end product of lipid peroxidation (Heath and Packer 1968;Loreto and Velikova 2001;Sunkar et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In plant cells, environmental stressors, such as drought, salinity, extreme temperatures and heavy metals, cause a rapid and excessive accumulation of reactive oxygen species that further cause lipid peroxidation (Sunkar et al 2003). The levels of lipid peroxidation in plant cells were assayed with the thiobarbituric acid test, which determines the amounts of MDA as end product of lipid peroxidation (Heath and Packer 1968;Loreto and Velikova 2001;Sunkar et al 2003). A recent study also demonstrated that the reduced levels of MDA accumulation were correlated with the elevated stress tolerance in the transgenic overexpressors of several Arabidopsis ALDH genes (Kotchoni et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stress can lead to the accumulation of toxic degradation products, including aldehydes (Srivastava et al 2002). The overexpression of aldehyde dehydrogenase genes (ALDHs) from A. thaliana catalyzed the dehydrogenation of aldehydes and enhanced the salt tolerance of transgenic plants (Sunkar et al 2003). Thus it is clear that in terms of the response of industrial hemp to salt stress, small molecule metabolism pathways deserve our attention.…”
Section: Discussionmentioning
confidence: 99%